2018
DOI: 10.11113/sh.v10n3-4.1548
|View full text |Cite
|
Sign up to set email alerts
|

Latar Belakang Guru Tahfiz di Institusi Tahfiz Persendirian Negeri Selangor

Abstract: This study is aimed at obtaining and gathering information on the background of teachers who teach at tahfiz private institutions throughout the state of Selangor regarding their age, education level, origin, status of post, teaching experience, salary or monthly allowance they received the virtues they earn. The study was quantitative in which a total of 90 questionnaires were distributed to respondents. Of this total, only 86 forms were returned and analyzed Quantitative data was analyzed descriptively using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Several previous studies had found that there was no uniformity of syllabus or learning modules, as well as future problems of these students after their graduation [4], [5]. Moreover, the study by Ghani, et al [9] found that most of these tahfiz schools had different objectives, approaches and management style. As for the school climate variables, it was found to be at a moderate level.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several previous studies had found that there was no uniformity of syllabus or learning modules, as well as future problems of these students after their graduation [4], [5]. Moreover, the study by Ghani, et al [9] found that most of these tahfiz schools had different objectives, approaches and management style. As for the school climate variables, it was found to be at a moderate level.…”
Section: Discussionmentioning
confidence: 98%
“…The absence of a standardized appointment scheme for the teachers had also been a constraint factor [8]. Moreover, the study by Ghani, et al [9] found that most of these tahfiz schools have different objectives, approaches, and management. However, there has not been an integrated and in-depth study that examines the basic things related to tahfiz institutions such as the basic factors that lead to the establishment of tahfiz institutions and looking at important aspects of students such as academic attitude and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…PTS managers feel that they have to face significant financial difficulties due to inadequate financial resources from student fees, public donations, organizational donations and so on. The results showed that the largest contribution to the construction Tahfiz institutions was public donation which involved 19 institutions (42.2%) followed by private capital funds involving 13 institutions (28.9%), 8 institutions (17.7%) from waqf and 5 institutions (11.2%) received assistance from specific organizations (Abd Ghani, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, a PTS may receive financial assistance from donations, government aid, and religious institutions. A study conducted by Abd Rahman Abd Ghani (2010) on PTSs in Selangor found that the most significant contribution to the founding of PTS institutions comes from community donations involving 19 institutions (42.2%), followed by private capital involving 13 institutions (28.9%), eight institutions (17.7%) from waqf sources, and five institutions (11.2%) receiving assistance from specific organizations.…”
Section: Introductionmentioning
confidence: 99%